Climate-Induced Displacement and International Human Rights Law: Addressing Legal Gaps in Protecting Environmental Migrants - Ginting, Grenaldo; Ginanjar, Seandy; Andi, Andi; Lindawati, Lindawati; Sumilat, Rohyani Rigen Is (Jurnal Smart Hukum (JSH), 2026)
Climate change has emerged as a significant driver of human displacement, forcing millions of people to leave their homes due to environmental degradation, extreme weather events, and rising sea levels. This study examines the legal protection gaps facing environmental migrants under international human rights law through a comprehensive qualitative analysis. The research employed document analysis, case study examination, and policy review to investigate how current international legal frameworks fail to adequately protect climate-displaced persons. Key findings reveal that the 1951 Refugee Convention excludes environmental displacement from its protection scope, leaving millions without legal status or rights. The landmark Teitiota v. New Zealand case established important precedent recognizing climate change as a potential trigger for non-refoulement obligations under international human rights law, particularly Article 6 of the International Covenant on Civil and Political Rights. However, significant gaps persist in complementary protection mechanisms, regional frameworks, and national implementation. The study identifies 218 million internal displacements globally due to weather-related disasters between 2013-2023, with an estimated 170 million people potentially displaced by 2050. Legal analysis demonstrates that while international human rights law provides broader protection potential than refugee law, extraterritorial obligations remain unclear and application inconsistent. The research concludes that comprehensive legal reform is urgently needed, including expanded complementary protection mechanisms, clearer non-refoulement obligations for climate displacement, and strengthened regional cooperation frameworks to address this growing humanitarian crisis.